IMPACT OF CLIMATE CHANGE ON AGRICULTURE AND LIVESTOCK: POLICY FEEDBACK FROM GRASS ROOTS - Bibi Hanifa; Dr. Abid Ghafoor Chaudhry (International Journal of Contemporary Issues in Social Sciences, 2024)
Title of the research is “Impact of Climate Change on Agriculture and Livestock: Policy Feedback from Grass Roots”. Locale of the research was Islamabad. The research objectives were to study the Impact of Climate Change on Agriculture and Livestock. Secondly, it aimed to explore appropriate measures for better use of Climate Change on Agriculture and Livestock. Thirdly, to study the problems and practices of stakeholders at grass root level and policy feedback from them. For the purpose of this study, a researcher used exploratory methodology and a qualitative method. Researcher collected data through the methods of interviews (interview guide), observations and focus group discussions (FGD guideline). This research contributes significantly to policy making and provides a valuable resources for individuals, policy makers and researchers seeking knowledge in agriculture and livestock production. It strengthens people’s capacity in food production, environmental conservation and livestock management.